The Effect of Exposure to Violent Video Games on Students’ Aggressive Tendencies - Wa Ode Lili Andriani Nasri; Puji Gusri Handayani; Susiati Susiati; Christine Masada Hirashita Tobing; Nurul Fajri; Reggiana Brescia; Yuda Syahputra (Kuras Institute, 2025)
The rapid development of digital technology has made online games a part of students' daily lives, including games containing violent elements. This phenomenon raises concerns because exposure to violent games is suspected of contributing to increased aggressive behavior among adolescents. Therefore, this study aims to determine the effect of violent games on the aggressive behavior of junior high school students. This study used a quantitative approach with a correlational design. The study sample consisted of 282 junior high school students spread across three provinces, namely West Sumatra, Jakarta, and Southeast Sulawesi, consisting of 121 male students and 161 female students. This study used two scales: the violent game scale and the aggressiveness scale. Data analysis was conducted through simple linear regression analysis. The results showed that playing violent games significantly influenced aggressive behavior. The coefficient of determination (R Square = 0.253) indicated that 25.3% of students' aggressive behavior was explained by the intensity of playing violent games, while the rest was influenced by other factors. The implications of this research are the need for active participation by schools, parents, and the community in monitoring and providing alternative positive activities that can reduce students' exposure to violent games.